APLIKASI PENGENDALIAN MUTU PROYEK EPC (STUDI KASUS : PROYEK EPC 1, BLOK CEPU) - Febriyanto, Agus Tri Wahyu; Wibowo, Robertus Kurniawan Wisnu Aji; Wibowo, M. Agung; Santoso, Tanto Djoko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
EPC Project is one form of the concept of project management delegate responsibility for the activities of design / design (Engineering), procurement of material / equipment (Procurement) and the construction (Construction) to the EPC contractor. These projects are often found in large-scale projects, commonly known by the term special projects, such as construction or manufacturing industries such as oil refineries, fertilizer plants, which require a large investment in the thousands of items and activities. EPC Project quality control system is very interesting to note given the number and types of activities that the EPC contractor faced so much beyond the capacity of traditional projects. For example, this research takes a case study in EPC Project 1 Banyu Urip, Cepu Block. The purpose and objective of this thesis is to investigate the process scheme engineering, procurement, and construction EPC project, distinguishing characteristics of quality management systems in the EPC projects with traditional project, as well as to determine the function of the quality of a traditional and EPC projects, whether prioritizing Quality Inspection, Quality Control, Quality Assurance, or Total Quality Management. The survey results revealed that the control system is more complex EPC projects than in traditional projects, because it has special handling, as well as every detail of the work has reference document as proof of the quality of quality have been met, except that there are a variety of disciplines involved so we need a coordination good in each discipline. Either the EPC project or the traditional project implementing quality function based Quality Inspection, Quality Control, and Quality Assurance that the owner was completely satisfied with the results of the EPC contractor's performance even though there are thousands of jobs that need to be addressed.